PENGATURAN PERSEROAN TERBATAS TERHADAP KASUS-KASUS DI BERBAGAI NEGARA DALAM HAL TANGGUNG JAWAB TERBATAS ATAU LIMITED LIABILITY - Sandra Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Limited companies as a business entity must carry out business activities. Doing business activities means running a company. Business activities carried out by limited liability companies are in the economic field with the aim of obtaining profits / profits. This paper wants to discuss how the characteristics of a Limited Company are in comparison with other countries and the concept of limited liability or limited liability. The research method used is normative juridical which concludes that there are several elements of difference with other countries that make it different from Indonesia, while the concept of limited liability or limitatief aansprakelijheid is a fundamental instrument in company law. The concept cannot be separated from the piercing principle of the corporate veil or that can be interpreted as